Observed Differences between Males and Females in Surgically Treated Carpal Tunnel Syndrome Among Non-manual Workers: A Sensitivity Analysis of Findings from a Large Population Study. Issue 4 (20th March 2018) - Farioli, Andrea; Curti, Stefania; Bonfiglioli, Roberta; Baldasseroni, Alberto; Spatari, Giovanna; Mattioli, Stefano; Violante, Francesco Saverio
Abstract: Objectives: We aimed at assessing whether differences among males and females in carpal tunnel syndrome (CTS) epidemiology might be attributable to segregation with respect to occupational biomechanical exposures or differential access to care by sex. Methods: We analysed surgically treated cases of CTS occurring among non-manual workers in Tuscany between 1997 and 2000. We conducted a Monte Carlo simulation to estimate the difference in occupational biomechanical exposures between males and females necessary to explain the observed incidence rate ratios. We also accounted for the sex-specific probability of receiving surgery after the diagnosis of CTS, as women were reported to be more likely to undergo surgery in a subset of our study population. We quantified the hypothetical biomechanical overload through the hand activity level (HAL) metric proposed by the American Conference of Governmental Industrial Hygienists. To quantify the effect of HAL on CTS risk, we assumed a prior distribution based on findings from two large cohort studies of industrial workers. Results: After adjustment for the probability of receiving surgery, women showed a 4-fold incidence of CTS as compared with men. To explain this association among non-manual workers, women should have an average value of HAL at least 5 points higher. Conclusions: Our analysis does not support the hypothesis that the difference in CTS incidence between males and females is entirely attributable to occupational risk factors or to differential access to surgery. The causal pathway between sex and CTS might include more determinants such as hormonal factors, anthropometric characteristics, and non-occupational exposure to biomechanical overload (e.g. household tasks).